Comparing spatial conservation prioritization methods with site‐ versus spatial dependency‐based connectivity. Issue 2 (16th November 2022) - Muenzel, Dominic; Critchell, Kay; Cox, Courtney; Campbell, Stuart J.; Jakub, Raymond; Chollett, Iliana; Krueck, Nils; Holstein, Daniel; Treml, Eric A.; Beger, Maria
Abstract: Larval dispersal is an important component of marine reserve networks. Two conceptually different approaches to incorporate dispersal connectivity into spatial planning of these networks exist, and it is an open question as to when either is most appropriate. Candidate reserve sites can be selected individually based on local properties of connectivity or on a spatial dependency‐based approach of selecting clusters of strongly connected habitat patches. The first acts on individual sites, whereas the second acts on linked pairs of sites. We used a combination of larval dispersal simulations representing different seascapes and case studies of biophysical larval dispersal models in the Coral Triangle region and the province of Southeast Sulawesi, Indonesia, to compare the performance of these 2 methods in the spatial planning software Marxan. We explored the reserve design performance implications of different dispersal distances and patterns based on the equilibrium settlement of larvae in protected and unprotected areas. We further assessed different assumptions about metapopulation contributions from unprotected areas, including the case of 100% depletion and more moderate scenarios. The spatial dependency method was suitable when dispersal was limited, a high proportion of the area of interest was substantially degraded, or the target amount of habitat protected was low. Conversely, when subpopulations were well connected, the 100% depletion was relaxed, or more habitat was protected, protecting individual sites with high scores in metrics of connectivity was a better strategy. Spatial dependency methods generally produced more spatially clustered solutions with more benefits inside than outside reserves compared with site‐based methods. Therefore, spatial dependency methods potentially provide better results for ecological persistence objectives over enhancing fisheries objectives, and vice versa. Different spatial prioritization methods of using connectivity are appropriate for different contexts, depending on dispersal characteristics, unprotected area contributions, habitat protection targets, and specific management objectives. Comparación entre los métodos de priorización de la conservación espacial con sitio y la conectividad espacial basada en la dependencia Resumen: La dispersión larval es un componente importante de las redes de reservas marinas. Existen dos estrategias conceptualmente distintas para incorporar la conectividad de la dispersión en la planeación espacial de estas redes y es una pregunta abierta cuándo alguna de las dos es la más apropiada. Los sitios candidatos a reserva pueden ser seleccionados individualmente con base en las propiedades locales de la conectividad o en la estrategia espacial basada en la dependencia que consiste en seleccionar grupos de fragmentos de hábitat con un vínculo fuerte. La primera estrategia actúa sobre sitios individuales, mientras que la segunda actúa sobre pares de sitios vinculados. Usamos una combinación de simulaciones de dispersión larval que representaban a diferentes paisajes marinos y estudios de caso de modelos biofísicos de dispersión larval en la región del Triángulo de Coral y en la provincia de Sulawesi Sudoriental, Indonesia, para comparar el desempeño de estos dos métodos en el software de planeación espacial Marxan. Exploramos las implicaciones del desempeño del diseño de la reserva de diferentes distancias y patrones de dispersión basados en el establecimiento del equilibrio de larvas en las áreas protegidas y sin protección. Además, analizamos las suposiciones sobre las contribuciones metapoblacionales de las áreas sin protección, incluyendo el caso de la reducción al 100% y escenarios más moderados. El método de la dependencia espacial fue adecuado cuando la dispersión estuvo limitada, una proporción elevada del área de interés estaba sustancialmente degradada o era baja la cantidad meta de hábitat protegido. Al contrario, cuando las subpoblaciones estaban bien conectadas, la reducción al 100% estuvo relajada, o si una mayor parte del hábitat estaba protegido, la protección de los sitios individuales con altos puntajes en las medidas de conectividad fue una mejor estrategia. Los métodos de dependencia espacial generalmente produjeron soluciones con una agrupación más espacial y con más beneficios dentro que fuera de las reservas en comparación con los métodos basados sitios. Por lo tanto, los métodos de dependencia espacial tienen el potencial de proporcionar mejores resultados para los objetivos de persistencia ecológica por encima de los objetivos de mejora de las pesquerías, y viceversa. Los diferentes métodos de priorización espacial que usan la conectividad son apropiados para contextos diferentes, dependiendo de las características de dispersión, las contribuciones del área sin protección, las metas de protección del hábitat y los objetivos específicos del manejo. 【摘要】: 幼体扩散是海洋保护区网络的一个重要组成部分。有两种基于不同概念的方法可以将扩散连接度纳入保护区网络的空间规划中, 而它们的适用情境仍存有争议。这两种方法包括根据连接度的局部属性来独立地选择候选保护区, 以及用基于空间依赖性的方法选择一片紧密连接的栖息地斑块。前者作用于单个位点, 而后者作用于相连的一对位点。我们利用代表不同海洋景观的幼体扩散模拟和珊瑚三角区及印度尼西亚东南苏拉威西的幼体扩散生物物理模型的案例研究, 比较了这两种方法在空间规划软件Marxan中的表现。研究根据幼体在保护区和非保护区的平衡定殖情况, 探讨了不同扩散距离和模式对保护区设计效果的影响。我们进一步评估了对来自非保护区的集合种群贡献的不同假设, 包括100%枯竭和更适中的情况。空间依赖性方法适用于以下情况:扩散受到限制, 感兴趣的地区有很大一部分严重退化, 或者受保护的栖息地目标数量较低。相反, 当亚种群相互连接, 100%枯竭的假设被放宽, 或是更多栖息地得到保护时, 保护连接度指标得分高的单个位点则会成为较好的策略。与基于位点的方法相比, 空间依赖性方法通常会产生更多空间上聚集的解决方案, 且在保护区内比在保护区外有更多益处。因此, 空间依赖性方法可能为生态续存目标提供更好的结果, 而非有利于渔业目标, 反之亦然。根据扩散特征、未受保护地区的贡献、栖息地保护目标和具体的管理目标, 基于连接度的不同空间优先保护方法也适合于不同的情况。【翻译:胡怡思;审校:聂永刚】